2012
DOI: 10.2478/v10181-012-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacteria of the genus Staphylococcus isolated from the eggs of Japanese quail (Coturnix coturnix japonica)

Abstract: The study attempted to analyse and characterize bacteria of the genus Staphylococcus isolated from the surface and contents of quail eggs, taking into account their phenotypic properties, biochemical reactions, antibiotic sensitivity patterns, and PCR to test for the presence of the mecA gene, which is responsible for resistance to methicillin. The study included 45 strains of the genus Staphylococcus isolated from the whites, yolks and shells of table quail eggs. The results obtained indicate that a fairly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Taking these criteria into account, the presence of pathogenic bacteria in food, including table chicken eggs, may pose a serious health problem (food poisoning and foodborne infections), considering the fact that many foods containing eggs or egg products undergo no thermal treatment, or thermal treatment insufficient to neutralise these pathogens (3,21). The present study revealed a moderately high rate of Staphylococcus contamination of table chicken eggs, with S. aureus accounting for 7.6% of isolates and 9.5% strains, which showed extremely close correlation to S. aureus with the exception of coagulase production.…”
Section: Discussionmentioning
confidence: 99%
“…Taking these criteria into account, the presence of pathogenic bacteria in food, including table chicken eggs, may pose a serious health problem (food poisoning and foodborne infections), considering the fact that many foods containing eggs or egg products undergo no thermal treatment, or thermal treatment insufficient to neutralise these pathogens (3,21). The present study revealed a moderately high rate of Staphylococcus contamination of table chicken eggs, with S. aureus accounting for 7.6% of isolates and 9.5% strains, which showed extremely close correlation to S. aureus with the exception of coagulase production.…”
Section: Discussionmentioning
confidence: 99%
“…Fowl/poultry including domestic chickens [58,59,60,61,62], turkeys [61,63], Japanese quails ( Coturnix coturnix japonica , [64,65])…”
Section: Introductionmentioning
confidence: 99%
“…Only two species, S. aureus and S. haemolyticus were detected at the final step of the frozen line, whereas S. epidermidis disappeared. also result from protein sources such as fresh beef, soybean curd, shells, and the yolk of quail eggs used to prepare fillings (Ananchaipattana et al, 2012;Goja, Ahmed, Saeed, & Dirar, 2013;Pyzik & Marek, 2012). Staphylococci are normally found in the air, dust, water, food, humans and animals, and on environmental surfaces (Hait, Tallent, Melka, Keys, & Bennett, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci sp. also result from protein sources such as fresh beef, soybean curd, shells, and the yolk of quail eggs used to prepare fillings (Ananchaipattana et al, 2012;Goja, Ahmed, Saeed, & Dirar, 2013;Pyzik & Marek, 2012). Therefore, special care should be taken of these raw materials with strong control procedures.…”
Section: Discussionmentioning
confidence: 99%